2007
DOI: 10.1021/jf070719r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gastric H+,K+-ATPase andHelicobacter pyloriGrowth by Phenolic Antioxidants ofCurcuma amada

Abstract: Gastric ulcer is the most prevalent gastrointestinal disorder, resulting from oxidative stress, Helicobacter pylori infection, up-regulation of proton potassium ATPase (PPA) activity, down-regulation of gastric mucosal defense, etc. In this paper it is reported that phenolic fractions of Curcuma amada, commonly known as mango ginger, acted as potent inhibitors of PPA and H. pylori growth. Mango ginger free phenolics (MGFP) and mango ginger bound phenolics (MGBP) inhibited PPA at IC50 values of 2.2 +/- 0.21 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…A recent study has shown that the phenolic antioxidants of Curcuma amada (popularly known as mango ginger), which possesses antioxidative and antimicrobial properties against H. pylori, were capable of inhibiting the human gastric H + ,K + -ATPase activity that is responsible for acid secretion [59].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the phenolic antioxidants of Curcuma amada (popularly known as mango ginger), which possesses antioxidative and antimicrobial properties against H. pylori, were capable of inhibiting the human gastric H + ,K + -ATPase activity that is responsible for acid secretion [59].…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity of free and bound phenolics from mango ginger rhizomes has been reported by Siddaraju and Dharmesh (2007). Both free and bound phenolic fractions of mango ginger are effective in inhibiting H+, K+-ATPase activity and Helicobacter pylori growth.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The free phenolic acids (figure 4) present in mango ginger are caffeic (26%, 195 mg/g), gentisic (24%, 180 mg/g) and ferulic (20%, 150 mg/g) followed by gallic (10%, 75 mg/g), cinnamic (7%, 52.5 mg/g), protocatechuic (7%, 52.5 mg/g) and small amounts of syringic (4%, 30 mg/g) and p-coumaric acids (2%, 15 mg/g) (Siddaraju and Dharmesh 2007). It also contains bound phenolic compounds like ferulic acid (47%, 391.5 mg/g) and cinnamic acid (29%, 237 mg/g), p-coumaric acid (11%, 95 mg/g), syringic acid (5%, 38.8 mg/g), caffeic acid (4%, 30.7 mg/g), gallic acid (1%, 11.5 mg/g) and gentisic acid (1%, 4.9 mg/g).…”
Section: Phenolic Content In Mango Ginger Extractsmentioning
confidence: 99%
“…Biological activities Curcuma aeruginosa Antimicrobial [164] , cytotoxicity [152] ; antinociceptive, antipyretic [13] ; uterine relaxant [74] ; antioxidant [165] ; inhibition of nitric oxide production [166] ; and anti-inflammatory [153] Curcuma amada Antifungal and insecticidal [79] ; CNS depressant and analgesic [16,167] ; antiulcer [168] ; anti-tubercular [135] ; antioxidant, antimicrobial, cytotoxic and antiplatelet [20] ; anti-inflammatory [169] ; anticancer [170] ; and larvicidal [171] Curcuma angustifolia Antimicrobial, antiulcerogenic [172,173] ; antioxidant [155] ; antifungal and antibacterial [129] Curcuma aromatica Hypoglycemic [172] ; anti-Alzheimer [173] ; antioxidant [2] ; cytotoxicity [174] ; insecticidal [175] ; antiinflammatory [169] ; antibacterial [11] ; inhibition of nitric oxide production [176] ; antiproliferative [177] ; and gastroprotective [21] Curcuma australasica Inhibition of nitric oxide and prostaglandin production, anti-inflammatory, and cytotoxic [115] Curcuma caesia Smooth muscle relaxant [178] ; anxiolytic, CNS depressant and neuropharmacological [179,180] ; antimicrobial [151] ; antiulcerogenic [181] ; antitumor and antioxidant [116] ; anticancer [182] ; antihepatotoxicity and nephrotoxicity [...…”
Section: Plant Speciesmentioning
confidence: 99%